Job satisfaction moderate in self-leadership on job performance - Darma, I Nyoman Adi Setya; Surya, Ida Bagus Ketut; Suwandana, I Gusti Made (International research journal of management, IT and social sciences, 2019)
The purpose of this study is to analyze the effect of self-leadership on employee job satisfaction and to analyze the role of job satisfaction in moderating the effect of self-leadership on job performance. This study was classified as associative research (relationship) of self-leadership, job performance and job satisfaction at Tjendana Villa Seminyak with 56 respondents. This research analysis technique uses the Moderated Regression Analysis (MRA) Test. The implication of this research can be a company reference to design regulations and policies to improve job satisfaction by taking the Leadership and Job performance that may occur. Based on the results of the research analysis and the results of the discussion, the conclusions of this study are as follows, Self-leadership has a significant positive effect on job performance. Job satisfaction has a significant positive effect on job performance. Job satisfaction strengthens the effect of leadership on job performance.